2021
DOI: 10.1371/journal.pone.0260928
|View full text |Cite
|
Sign up to set email alerts
|

Case management programs for people with complex needs: Towards better engagement of community pharmacies and community-based organisations

Abstract: Introduction The objectives of this study were 1) to describe how case management programs engaged community pharmacies and community-based organisations in a perspective of integrated care for people with complex needs, and 2) to identify enablers, barriers and potential strategies for this engagement. Methods Using a descriptive qualitative design, individual interviews and focus groups with patients, healthcare providers and managers were analysed according to a mixed thematic analysis based on a deductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For the case management model in this study, the communication between nurses and patients was strengthened and improves the patient experience, increasing patient motivation to actively participate in the process of treatment and care and to effectively help patients recover [ 14 ]. This study found that old patients with lung scale-like cell cancer almost never actively communicated with medical staff at first, but communicated with other patients through social software (in a carefully-planned way), hiding signs of sickness and mental needs to reduce the heavy load on family members, but missing active guidance from nurses.…”
Section: Discussionmentioning
confidence: 99%
“…For the case management model in this study, the communication between nurses and patients was strengthened and improves the patient experience, increasing patient motivation to actively participate in the process of treatment and care and to effectively help patients recover [ 14 ]. This study found that old patients with lung scale-like cell cancer almost never actively communicated with medical staff at first, but communicated with other patients through social software (in a carefully-planned way), hiding signs of sickness and mental needs to reduce the heavy load on family members, but missing active guidance from nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for the CBR were developed based on formal research studies, diverse experiences of disability, best practices drawn from similar approaches, as well as the research team’s own expertise [ 24 ]. Interdisciplinary case management (ICM) : Case management is a collaborative, client-driven process characterized by exchanging ideas and opinions among team members for the provision of quality health and support services [ 25 ]. Through ICM, care teams have a shared vision on the content of the care, enabling consensus among stakeholders and reducing duplication of services.…”
Section: Methodsmentioning
confidence: 99%
“…Interdisciplinary case management (ICM) : Case management is a collaborative, client-driven process characterized by exchanging ideas and opinions among team members for the provision of quality health and support services [ 25 ]. Through ICM, care teams have a shared vision on the content of the care, enabling consensus among stakeholders and reducing duplication of services.…”
Section: Methodsmentioning
confidence: 99%